PREFERENSI TAMU TERHADAP PELAYANAN ROOM ATTENDANT DI FOUR POINTS BY SHERATON BALI, UNGASAN - I Gede Suarsana Fradiana; Ni Nyoman Suci Arthini; Anak Agung Istri Ratna Sari Wulan (Program Studi Manajemen Divisi Kamar, 2023)
Room attendant services are one of the parts of improving the quality of a hotel. One of the assessments that can be done is to check how well the services of the room attendant in a hotel are through guest preferences for room attendant services. This research was conducted to determine guest preferences for room attendant services at Four Points by Sheraton Bali Ungasan. This research used the descriptive qualitative descriptive method which used qualitative data gained from guest reviews of several online travel agents such as TripAdvisor and Booking.com. the result of this study indicates that guest preferences for room attendants are in the aspects of cleanliness, hospitality, and comfort which are proven from dust-free, odorless, and damp rooms as the standard of room attendant service which must be able to prepare rooms in on time, create a comfortable room atmosphere and still clean. In addition, room attendants are expected to be friendly and able to communicate well, not only with employees but also with guests.